2013
DOI: 10.1155/2013/268407
|View full text |Cite
|
Sign up to set email alerts
|

Serum N‐Glycan Profiling Predicts Prognosis in Patients Undergoing Hemodialysis

Abstract: Background. The aim of this study is to evaluate the usefulness of serum N-glycan profiling for prognosis in hemodialysis patients. Methods. Serum N-glycan analysis was performed in 100 hemodialysis patients in June 2008 using the glycoblotting method, which allows high-throughput, comprehensive, and quantitative N-glycan analysis. All patients were longitudinally followed up for 5 years. To evaluate the independent predictors for prognosis, patients' background, blood biochemistry, and N-glycans intensity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…N -glycomics was performed as described previously. A 10-μL aliquot of the purified Igs fractions were analyzed using the glycoblotting method [ 11 , 12 , 15 , 33 ] on a Sweetblot instrument (System Instruments, Hachioji, Tokyo, Japan). Then, the resulting benzyloxiamine (BOA)-labelled glycans were detected by matrix-assisted laser desorption time-of-flight (MALDI-TOF) mass spectrometry (Ultraflex 3 TOF/TOF mass spectrometer; Bruker Daltonics, Bremen, Germany) ( Figure A1 a–f).…”
Section: Methodsmentioning
confidence: 99%
“…N -glycomics was performed as described previously. A 10-μL aliquot of the purified Igs fractions were analyzed using the glycoblotting method [ 11 , 12 , 15 , 33 ] on a Sweetblot instrument (System Instruments, Hachioji, Tokyo, Japan). Then, the resulting benzyloxiamine (BOA)-labelled glycans were detected by matrix-assisted laser desorption time-of-flight (MALDI-TOF) mass spectrometry (Ultraflex 3 TOF/TOF mass spectrometer; Bruker Daltonics, Bremen, Germany) ( Figure A1 a–f).…”
Section: Methodsmentioning
confidence: 99%
“…A 10-µL aliquot of whole serum or a Igs fraction purified from whole serum was processed by using the glycoblotting method [8][9][10][11][12][13][14]21] and a controlled automated SweetblotTM instrument (System Instruments, Hachioji, Japan). Then, the resulting BOA-labeled glycans were detected by MALDI-TOF MS (Ultraflex 3 TOF/TOF mass spectrometer; Bruker Daltonics, Bremen, Germany) (Figure 8).…”
Section: Glycoblotting Methods and Mass Spectrometrymentioning
confidence: 99%
“…Serum N -glycomics was performed as described previously. A 10-μL aliquot of whole serum or a Igs fraction purified from whole serum was processed by using the glycoblotting method [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 21 ] and a controlled automated SweetblotTM instrument (System Instruments, Hachioji, Japan). Then, the resulting BOA-labeled glycans were detected by MALDI-TOF MS (Ultraflex 3 TOF/TOF mass spectrometer; Bruker Daltonics, Bremen, Germany) ( Figure 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…Glycosylation has an important role in various biological functions. Recently, our group demonstrated that high-throughput, comprehensive, and quantitative serum N -glycomics was a promising method to screen N -glycan for diagnostic and prognostic markers of several cancers [ 8 , 9 , 10 ] and was a promising predictive tool for patients undergoing hemodialysis [ 11 ]. However, the use of serum N -glycans as a predictive biomarker of ABMR has not yet been tested.…”
Section: Introductionmentioning
confidence: 99%